2023
DOI: 10.3390/microorganisms11010229
|View full text |Cite
|
Sign up to set email alerts
|

Deletions across the SARS-CoV-2 Genome: Molecular Mechanisms and Putative Functional Consequences of Deletions in Accessory Genes

Abstract: The analysis of deletions may reveal evolutionary trends and provide new insight into the surprising variability and rapidly spreading capability that SARS-CoV-2 has shown since its emergence. To understand the factors governing genomic stability, it is important to define the molecular mechanisms of deletions in the viral genome. In this work, we performed a statistical analysis of deletions. Specifically, we analyzed correlations between deletions in the SARS-CoV-2 genome and repetitive elements and document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…This puzzling observation echoes with an observed evolutionary trend in SARS-CoV-2 accessory proteins: it is well-known that there are many deletions in the ORF7a-ORFb-ORF8 complex in SARS-CoV-2 [ 33 38 ]. Our recent analysis of deletion in the SAR-CoV-2 genome suggested that the density of deletions (the number of deletions divided by the gene length) for ORF7a and ORF8 is always much higher than that for other SARS-CoV-2 genes [ 39 ]. Interestingly, a prominent feature of all the studied deletions is that they predominantly located around the middle of the SARS-CoV-2 genes resembling the situation with a 29-nt deletion in SAR-CoV ORF8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This puzzling observation echoes with an observed evolutionary trend in SARS-CoV-2 accessory proteins: it is well-known that there are many deletions in the ORF7a-ORFb-ORF8 complex in SARS-CoV-2 [ 33 38 ]. Our recent analysis of deletion in the SAR-CoV-2 genome suggested that the density of deletions (the number of deletions divided by the gene length) for ORF7a and ORF8 is always much higher than that for other SARS-CoV-2 genes [ 39 ]. Interestingly, a prominent feature of all the studied deletions is that they predominantly located around the middle of the SARS-CoV-2 genes resembling the situation with a 29-nt deletion in SAR-CoV ORF8 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a prominent feature of all the studied deletions is that they predominantly located around the middle of the SARS-CoV-2 genes resembling the situation with a 29-nt deletion in SAR-CoV ORF8 . It should be noted that a hypervariability in SARS-CoV-2 ORF7A and ORF8 is not associated with mechanisms of deletions [ 39 ]. Thus, these deletions are likely to reflect recurrent searches of functional “space” of accessory protein combinations to achieve their more advantageous configurations.…”
Section: Discussionmentioning
confidence: 99%
“…The obvious pitfall of this approach is frequently missing recurrent mutations, reversals (backward mutations), and indels (insertions and deletions). However, the approach is useful for analyses of long insertions and deletions [28,30,31]. A substantially more sophisticated approach for the prediction of mutations is based on phylogenetic inferences [7] and allows detection of recurrent mutations and reversals.…”
Section: Reconstructions and Analyses Of Mutation Spectra: Methodolog...mentioning
confidence: 99%
“…Phylogenetic trees (i.e., Figure 2) can be inferred using various methods, yet all of them have certain limitations. As an example, the least squares distance and maximum parsimony approaches to predicting deletions in over 600 thousand SARS-CoV-2 genomes produced many false positive hits [30]. Inaccuracies of phylogenetic reconstructions and the difficulty of predicating the ancestral sequences that are used to infer mutations are well known [32,33].…”
Section: Reconstructions and Analyses Of Mutation Spectra: Methodolog...mentioning
confidence: 99%
See 1 more Smart Citation